The predictive role of lung clearance index on FEV1 decline in cystic fibrosis - Beste Özsezen; Ebru Yalçın; Nagehan Emiralioğlu; Hande Konşuk Ünlü; Dilber Ademhan Tural; Canan Caka; Birce Sunman; Deniz Doğru; Ugur Özçelik; Nural Kiper (The Turkish Journal of Pediatrics)
Background. The lung clearance index (LCI) is a sensitive lung function index that is used to detect early lung disease changes in children with cystic fibrosis (CF). This study aimed to define the predictive role of baseline LCI, along with other potential factors on the change in forced expiratory volume in one second (FEV1) during one-year follow-up in CF patients who had a percent predicted (pp) FEV1≥80.